Prediction of motor outcome using remaining corticospinal tract in patients with pontine infarct: Diffusion tensor imaging study. (2nd April 2016) - Jang, Sung Ho; Lee, Jun; Lee, Mi Young; Park, So Min; Choi, Won Hee; Do, Kyung Hee
Abstract: The aim of this study was to investigate the relationship between the remaining corticospinal tract (CST) as determined by diffusion tensor imaging (DTI) and 6-month motor outcome in patients with pontine infarct. Ratios of fractional anisotropy (FA), fiber number (FN), and CST area were calculated, and the FN ratio and CST area ratio showed significant correlation with all 6-month motor outcome. Thus, the remaining CST in the pons measured using DTI at early stage of stroke could predict motor outcome in patients with pontine infarct.